1986
DOI: 10.1093/oxfordjournals.eurheartj.a062052
|View full text |Cite
|
Sign up to set email alerts
|

Serum potassium concentrations are inversely related to ventricular, but not to atrial, arrhythmias in acute myocardial infarction

Abstract: In a study of 1033 consecutive patients with acute myocardial infarction, serum potassium concentrations were determined on admission to hospital and studied with respect to the subsequent occurrence of atrial fibrillation and flutter and of ventricular tachycardia and fibrillation. The study cohort fulfilled the inclusion criteria for the Norwegian timolol trial in which they later took part. In multivariate analysis, with serum potassium concentrations as a continuous variable, age, the presence of ventricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
1

Year Published

1988
1988
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 0 publications
1
9
1
Order By: Relevance
“…The progressive deleterious effects of hypokalemia in HF patients with CKD may also be mediated by aldosterone, which has been shown to cause myocardial fibrosis, diastolic dysfunction and disease progression in HF 3336. Although the effect of hypokalemia in the setting of acute myocardial infarction is well known,3739 little is known about the effect of hypokalemia in patients with chronic IHD. Although the prevalence of hypokalemia was lower in patients with IHD (Table 1, pre-match), the effects of hypokalemia were worse in those with IHD (Figure 3), suggesting that infarcted/ischemic myocardium may provide a more suitable substrate for the adverse effects of hypokalemia.…”
Section: Discussionmentioning
confidence: 99%
“…The progressive deleterious effects of hypokalemia in HF patients with CKD may also be mediated by aldosterone, which has been shown to cause myocardial fibrosis, diastolic dysfunction and disease progression in HF 3336. Although the effect of hypokalemia in the setting of acute myocardial infarction is well known,3739 little is known about the effect of hypokalemia in patients with chronic IHD. Although the prevalence of hypokalemia was lower in patients with IHD (Table 1, pre-match), the effects of hypokalemia were worse in those with IHD (Figure 3), suggesting that infarcted/ischemic myocardium may provide a more suitable substrate for the adverse effects of hypokalemia.…”
Section: Discussionmentioning
confidence: 99%
“…The data linking hypokalemia with arrhythmia and cardiac arrest in AMI are fairly strong, but the direct myocardial effect of increased circulating adrenaline is a possible confounder (38,39). Despite this, it is sensible to maintain a serum potassium concentration above 4.5 mmol/l during AMI.…”
Section: Magnesiummentioning
confidence: 99%
“…Longitudinal community studies have demonstrated an increased long-term risk of AF in patients with lower potassium or magnesium levels at baseline (3-5), although these observations have little clinical relevance to postoperative cardiac surgery patients. In one study of 1033 hospitalized patients with acute myocardial infarction (MI), lower serum potassium concentrations were related to ventricular but not atrial arrhythmias (6). The largest study to investigate serum electrolyte levels in cardiac surgery patients (n=500) showed that electrolyte disturbances are common on ICU admission, with 34% of patients exhibiting hypokalemia and 46% exhibiting hypomagnesemia, however subsequent postoperative electrolyte levels and arrhythmia occurrence were not examined (2).…”
mentioning
confidence: 99%